PERANCANGAN USER INTERFACE SISTEM INFORMASI DESA MENGGUNAKAN METODE GOAL-DIRECTED DESIGN (STUDI KASUS : DESA SUKAMANAH) - Pamungkas, Muhammad Giffari Raihan (2021)
Sukamanah Village, Baros District, Serang Regency, Banten requires a system design in the form of a user interface that is good and easily understood by village officials and villagers so that it can simplify and speed up the service process. So far, services to villagers are still carried out conventionally because many villagers do not understand information technology. This is at risk of causing long queues due to the time-consuming process. To make services to villagers faster, it requires a design of a user interfaces village information system that suits the needs of the Sukamanah village. This study aims to design a user interface based on the needs of the Sukamanah village in the village information system using the method Goal-Directed Design which consists of 6 phases. Phase research, looking for system requirements that are desired by users. Phase Modelling, looking for user characteristics by creating user personas. Phase requirements produce user scenarios and describe system requirements using Hierarchical Task Analysis. Phase framework definition, creating an interface structure in the form of wireframing. Phase refinement, perfecting the interface structure to a form high-fidelity. The development support phase is a qualitative testing phase for users using an assessment based on the System Usability Scale (SUS) to get feedback on the prototype of the village information system that suits your needs.